Analisis Perbandingan Kinerja Keuangan Sebelum Dan Saat Pandemi Covid- 19 Pada Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia - Novita Eka Aprily Yanti; Agustina Widodo (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The results of this study evaluate before and after the COVID-19 outbreak, the financial performance of the beverage and food industry which has been listed on the IDX or the Indonesian Stock Exchange. The variables considered in this study include Solvability (DER), Profitability (ROA), Activity (WCTO), and Liquidity (CR) ratios. purposive sampling used in the sampling method with a total of 22 companies. Food and beverage companies listed on the IDX are the sample population from 2018 to 2021. This type of research data is formed by secondary data. The data in this study were analyzed with SPSS 22 using paired sample t-test. There is no comparison, according to the findings of this study's hypothesis testing.